Continuous electrocardiographic recording during exercise in young male diabetics. A computer study. Issue 3 (March 1975) - Campbell, I W; McGarry, S; Smith, D N; Neilson, J M; Clarke, B F
Abstract : Forty selected young patients with diabetes of medium to long duration and 26 control subjects without clinical evidence of ischaemic heart disease were studied using a new and sensitive technique of electrocardiographic recording during exercise with continuous computation of the time course of the ST-T segment changes to detect possible early ST depression indicative of ischaemia. Although no such evidence was found, significant differences in the diabetics were observed in the heart rate and ST-T segment, the latter changes having not been previously reported but which may be attributed to ischaemia or alternatively to autonomic neuropathy in the "presymptomatic" phase.